THE INFLUENCE OF EXCHANGE RATES, INTEREST RATES, AND BANK INDONESIA SHARIA CERTIFICATES ON THE INDONESIAN SHARIA STOCK INDEX - Engelia Putri Natasya; Agus Eko Sujianto; Fatma Nur Maulidiyah; Dinda Oktafiani; Siti Ro’isa Ningtyas (Fakultas Ekonomi dan Bisnis Universitas Wijaya Putra, 2023)
The Indonesian Sharia Stock Index is used to assess the value of stocks in accordance with sharia law in Indonesia, covering all stocks traded on the IDX. This study aims to examine how the Indonesia Shariah Stock Index is affected by interest rates, exchange rates and Shariah-compliant Bank Indonesia Certificates between 2016 and 2021. Using up to 72 samples, quantitative techniques were applied to the population of all data from currency exchange rates, interest rates, SBIS and ISSI. The technique of multiple linear regression analysis is used to analyze the secondary data of this study. The conclusion of this research is that the ISSI is negatively affected by the exchange rate, the ISSI is not affected by interest rates, and SBIS has a negative influence on the ISSI. Simultaneously the three variables affect the ISSI and their interconnections create the environment in which companies and investors operate. Changes in these factors can create a domino effect that affects the overall health and performance of the Islamic stock market. Keywords: Exchange Rates, Interest Rates, SBIS, ISSI